Benthic amphipods (Amphipoda: Gammaridea and Corophiidea) from the Mexican southeast sector of the Gulf of Mexico: checklist, new records and zoogeographic comments - Paz-Ríos, Carlos E.; Ardisson, Pedro-Luis (Zootaxa, 2013)
The southeast region of theGulf of Mexicois considered to be biologically important, because it is a connection and transition zone between theCaribbeanand theGulf of Mexico, harboring great marine biodiversity. Nevertheless, benthic amphipods have been poorly studied in the Mexican southeast sector of theGulf of Mexicowith few studies listing species. The aim of this study is to provide an update checklist of species for the Mexican southeast sector (based on literature review and records from the present study) as well as a brief zoogeographical analysis for theGulf of Mexicoamphipod fauna, putting them in context with the fauna on the tropical westernAtlantic. Fifty-five species were listed for the Mexican southeast sector; 36 of them showed a geographical extension to the Yucatan continental shelf representing 23 new records for the Mexican southeast sector, nine for the southeast region and four for the Gulf of Mexico. Based on the zoogeographical analysis, there is support of the application of Carolinian andCaribbeanzoogeographic provinces to amphipods in theGulf of Mexico.